Manholes as an important breeding sites for Culex mosquitoes in Gazipur City Corporation, Bangladesh (Bangladesh Journal of Zoology, 2018)
A longitudinal study in under constructing Manholes (considered as mosquito breeding trap of the study area) in a newly constructing road in the ward number 35 was conducted in the post monsoon period of 2016. Four species of mosquito population were available in the stagnant water of temporary breeding sites. Among them Cx. quinquefasciatus was the dominant species (98.6%) followed by Cx. tritaeniorhynchus (0.5%), Ar. subalbatus (0.5%) and Cx. fuscocephala (0.4%). Though the breeding sites were temporary and stayed until finishing the construction, yet the results indicated the abundant population of available mosquitoes including status of key species in the urban area of the city corporation.Bangladesh J. Zool. 45(2): 139-148, 2017